2020
DOI: 10.2147/ijn.s254342
|View full text |Cite
|
Sign up to set email alerts
|

<p>An AFM-Based Nanomechanical Study of Ovarian Tissues with Pathological Conditions</p>

Abstract: Background: Different diseases affect both mechanical and chemical features of the involved tissue, enhancing the symptoms. Methods: In this study, using atomic force microscopy, we mechanically characterized human ovarian tissues with four distinct pathological conditions: mucinous, serous, and mature teratoma tumors, and non-tumorous endometriosis. Mechanical elasticity profiles were quantified and the resultant data were categorized using K-means clustering method, as well as fuzzy C-means, to evaluate elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…In this work we eliminate the need for staining and ad hoc AFM measurements entirely: localisation of measured areas has been fine-tuned to obtain precisely registered pairs of unstained tissue images and EM maps, and these pairs were used to train a style transfer deep learning architecture to infer the sample-wide EM of tissue sections from low-resolution grayscale microscopy images. The resulting EM distributions contain the nanomechanical signatures of the underlying tissue pathology identified previously, 27,[33][34][35] and unsupervised clustering of distribution parameters provides an accurate prediction of tissue pathology, validated through pathologist assessment of post hoc stained sections. The use of a well-optimized prediction algorithm allows for much more rapid diagnoses compared to time-intensive diagnostic methods such as IFS analysis or ad hoc AFM measurements.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this work we eliminate the need for staining and ad hoc AFM measurements entirely: localisation of measured areas has been fine-tuned to obtain precisely registered pairs of unstained tissue images and EM maps, and these pairs were used to train a style transfer deep learning architecture to infer the sample-wide EM of tissue sections from low-resolution grayscale microscopy images. The resulting EM distributions contain the nanomechanical signatures of the underlying tissue pathology identified previously, 27,[33][34][35] and unsupervised clustering of distribution parameters provides an accurate prediction of tissue pathology, validated through pathologist assessment of post hoc stained sections. The use of a well-optimized prediction algorithm allows for much more rapid diagnoses compared to time-intensive diagnostic methods such as IFS analysis or ad hoc AFM measurements.…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies that identified the nanomechanical signatures of disease did so through a large number of "blind" AFM measurements of bulk (≥1 mm thick) tissue sections, statistically correlating the findings with post hoc histopathology. 27,[33][34][35] Fig. 1 shows the general procedure for measuring tissue samples using an AFM; the cantilever assembly occludes much of the camera's field-of-view (FOV), reducing the contrast of the resulting image.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AFM was used to mechanically characterize four human ovarian tissues distinct pathological conditions: mucinous and serous cystadenoma, mature teratoma, and endometriosis [ 85 ]. As expected, the authors found considerable heterogeneity within the tissue, but they could observe some differences in elastic modulus values of the cellular part and extracellular matrix among the four ovarian samples.…”
Section: The Mechanical Properties Of the Cells And Tissues In Female Reproductive Disordersmentioning
confidence: 99%
“…These findings support that mechanical measurements represent a valuable tool to delineate the mechanical phenotypes of cells and tissue in ovary tumors. Based on the biomechanical properties, a screening approach could be employed to complement standard biopsy procedures, offering a novel and quantitative diagnostic approach to help cancer grading/classification, with an unbiased evaluation of the sample [ 85 , 86 ].…”
Section: The Mechanical Properties Of the Cells And Tissues In Female Reproductive Disordersmentioning
confidence: 99%
“…23 Also, both rheological and MRE measurements provide only average bulk mechanical properties from the entire volume of cells and ECM in the sample. To attain nanoscale and single-cell resolution, atomic force microscopy (AFM) must be used, and has been reported previously 7,[24][25][26] for different tissue types. Reports have clearly indicated that AFM might be successfully used in research on brain tumor tissue to understand the mechanopathology of this deadly disease.…”
Section: Introductionmentioning
confidence: 99%